International directory of company histories. Volume 173. - Pederson, Jay P.; Gale Group (Farmington Hills, Mich. St. James Press, a part of Gale, Cengage Learning, 2016)
Provides histories of companies that are a leading influence in a particular industry or geographic location. For students, job candidates, business executives, historians and investors.
3D Robotics, Inc. -- 3G Capital Partners LP -- 3i Group PLC -- A&G Realty Partners, LLC -- Abaxis, Inc. -- AbbVie Inc. -- Accion International -- Acetificio Acetum S.r.l. -- ACT 1 Group Inc. -- Adamas Pharmaceuticals, Inc. -- Adams Diversified Equity Fund, Inc. -- Adeptus Health Inc. -- AgustaWestland S.p.A. -- Alleanza Assicurazioni S.p.A. -- Andrews Kurth, LLP -- Aquascape, Inc. -- Beal Bank, SSB -- Betabrand Corporation -- Big Machine Label Group -- BioMarin Pharmaceutical Inc. -- bioMerieux S.A. -- Birchbox, Inc. -- Bodybuilding.com LLC -- Boliviana de Aviacion -- Boston Market Corporation -- Bricorama S.A. -- Britvic PLC -- C&J Clark International Ltd. -- Canary Wharf Group plc -- Cascades Inc. -- Chattem, Inc. -- China Shenhua Energy Company Ltd. -- Christie's International PLC -- Citizen Holdings Company Ltd. -- Cobalt Boats, LLC -- Columbian Mutual Life Insurance Company, Inc. -- Contango Oil & Gas Company -- Covanta Holding Corporation -- Credit Agricole S.A. -- CSR Limited -- DJI Technology Ltd. -- East Penn Manufacturing Co., Inc. -- Edipresse Group -- Electricity Generating Authority of Thailand -- Exelis Inc. -- fastjet Plc -- First Hawaiian Bank -- Fisk Corporation -- Franke Holding AG -- Freixenet S.A. -- Frontier Co-op -- Fuel Tech, Inc. -- Galenica AG -- GAME Digital plc -- George Weston Limited -- Gulf Air Company -- Health Communications, Inc. -- Hirshleifer's Inc. -- HNI Corporation -- The Honest Company -- Huntingdon Life Sciences Group plc -- iCIMS, Inc. -- Imgur, LLC -- IMS Health, Inc. -- InCube Labs, LLC -- Interconexion Electrica S.A. E.S.P. -- Iran Khodro Company -- K1 Speed, Inc. -- KB Home -- Kforce Inc. -- Kirkland & Ellis LLP -- Koninklijke Tichelaar Makkum BV -- Korber AG -- Lightspeed Venture Partners -- Mapletree Logistics Trust -- Mercy Corps, Inc. -- Middle East Airlines-Air Liban S.A.L. -- Moleskine SpA -- New Dominion, LLC -- New Relic, Inc. -- Nok Airlines Public Company Limited -- Nuts.com, Inc. -- Parrot S.A. -- PillPack, Inc. -- Polycom, Inc. -- Portage, Inc. -- Premier Foods plc -- Razor & Tie Direct, L.L.C. -- Roark Capital Group Inc. -- Sigma Alimentos, S.A. de C.V. -- Sollers, OJSC -- Splunk Inc. -- Standard General L.P. -- Thirty-One Gifts LLC -- Viceroy Hotel Group LLC -- Vitra AG -- WesBanco, Inc. -- Westgate Resorts Ltd. -- Yacimientos Petroliferos Fiscales Bolivianos S.A. -- Ziferblat.
Includes bibliographical references and indexes.
Keywords: Big business -- History -- Directories; Business enterprises -- History -- Directories; Corporations -- History -- Directories